2022
DOI: 10.3390/nu14061262
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Olfactory Function and BMI in Normal Weight Healthy Subjects and Patients with Overweight or Obesity

Abstract: Smell plays a critical role in food choice and intake by influencing energy balance and body weight. Malnutrition problems or modified eating behaviors have been associated with olfactory impairment or loss. The obesity epidemic is a serious health problem associated with an increased risk of mortality and major physical comorbidities. The etiopathogenesis of obesity is complex and multifactorial, and one of the main factors contributing to the rapid increase in its incidence is the environment in which we liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 77 publications
(102 reference statements)
5
20
0
Order By: Relevance
“…In conclusion, the present study for the first time found that olfactory processing – influencing physiological and neural systems involved with appetite and eating behaviors–is not only a critical component for the development and the maintenance of obesity 67,68 but–further–its performance tends to worsen with the increase of obesity stage. These findings enlarge those experiences evidencing that olfactory perception may progressively decrease with a linear relationship with measures of obesity, 40,69 its low‐grade chronic inflammation 60 and the pattern of hormones–such ghrelin and leptin–involved in the gut‐brain underpinning of olfactory processing 6,45,48,53 . However, future studies are needed to expand such notions to ameliorate clinical and research deepening of obesity‐related olfactory behavior with possible consequences on diagnosis, treatment and–especially–prevention of onset and development of obesity, thus opening possible future strategies involving multidisciplinary contributions.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In conclusion, the present study for the first time found that olfactory processing – influencing physiological and neural systems involved with appetite and eating behaviors–is not only a critical component for the development and the maintenance of obesity 67,68 but–further–its performance tends to worsen with the increase of obesity stage. These findings enlarge those experiences evidencing that olfactory perception may progressively decrease with a linear relationship with measures of obesity, 40,69 its low‐grade chronic inflammation 60 and the pattern of hormones–such ghrelin and leptin–involved in the gut‐brain underpinning of olfactory processing 6,45,48,53 . However, future studies are needed to expand such notions to ameliorate clinical and research deepening of obesity‐related olfactory behavior with possible consequences on diagnosis, treatment and–especially–prevention of onset and development of obesity, thus opening possible future strategies involving multidisciplinary contributions.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, previous studies demonstrated that individuals with obesity have a higher hedonic response to palatable food odors when compared to people of normal weight 10 and have decreased olfactory function. 1,[11][12][13][14][15]40 Especially odor sensitivity, which reflects perceptual function, 41 is decreased in individuals with obesity when compared to people with normal weight. 12,14 The mechanisms underpinning these alterations remain to be completely understood, however, it has been suggested that a reduced olfactory function may be linked to those hormonal and metabolic changes that are associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have highlighted patterns of unbalanced diets in patients with olfactory dysfunction, although these findings may reflect changes in intake and preference for specific items and not general patterns [ 18 ]. Moreover, obesity is also associated with lower olfactory test scores indicating that the causality of underlying mechanisms may be more complex [ 19 ].…”
Section: Discussionmentioning
confidence: 99%